Corrosion resistance of composite coating used for fastener protection. Issue 5 (2nd September 2019) - Lin, Zhifeng; Xu, Likun; Li, Xiangbo; Wang, Li; Guo, Weimin; Wu, Chuanjie; Yang, Yi
Abstract : Purpose: The purpose of this paper is to examine the performance of a fastener composite coating system, sherardized (SD) coating/zinc-aluminum (ZA) coating whether it has good performance in marine environment. Design/methodology/approach: In this paper, SD coating was fabricated on fastener surface by solid-diffusion method. ZA coating was fabricated by thermal sintering method. Corrosion behaviours of the composite coating were investigated with potentiodynamic polarization curves, open circuit potential and electrochemical impedance spectroscopy methods. Findings: Neutral salt spray (NSS) and deep sea exposure tests revealed that the composite coating had excellent corrosion resistance. Polarization curve tests showed that corrosion current density of the sample with composite coating was significantly decreased, indicating an effective corrosion protection of the composite coating. OCP measurement of the sample in NaCl solution demonstrated that the composite coating had the best cathodic protection effect. The good corrosion resistance of the composite coating was obtained by the synergy of SD and ZA coating. Practical implications: SD/ZA coating can be used in marine environment to prolong the life of carbon steel fastener. Social implications: SD/ZA composite coating can reduce the risk and accident caused by failed fastener, avoid huge economic losses. Originality/value: A new kind of composite coating was explored to protect the carbon steel fastener in marine environment. And the composite coating has the long-term anti-corrosion performance both in simulated and marine environment test.